The The Role of Lactate Level as Predictor of Mortality Critically Ill Children at Moewardi Hospital - Zilmi, Reza Ervanda; Pudjiastuti, Pudjiastuti; Siregar, Rustam (Journal of Maternal and Child Health, 2024)
Background: The prevalence of mortality among critically ill children worldwide, particularly in Indonesia, remains alarmingly high. Numerous studies have indicated that elevated lactate levels serve as a significant predictor of mortality in this vulnerable population. The primary objective of this study is to elucidate the predictive value of lactate levels in determining mortality risk among critically ill children. Subjects and Method: A cohort prospective study was conducted in children aged between 1 month and 18 years old who met the criteria for critically ill children treated in the Pediatric High care unit (PHCU) of Dr. Moewardi General Hospital, Surakarta from January to June 2023. The dependent variable was the mortality. The independent variable was lactate level serum. The data were collected using questionnaire and observation sheet. The cut off point of lactate level was determined with  ROC curve. Results: Among thirty critically ill pediatric patients, 43.3% died, while 56.7% survived. The deceased predominantly comprised females, with a mean age of 5.62 years (SD= 4.14). The mean lactate levels of those who died in the first hour, 6 hours, and 24 hours (Mean= 2.94; SD= 0.90) with a cut-off value of ≥2.35 mmol/L, (Mean= 3.20; SD= 0.50) with a cut-off value of ≥ 2.35 mmol/L and (Mean= 3.65; SD= 0.53) with a cut-off value of ≥2.95 mmol/L, respectively. The 24th hours lactate levels (persistence hyperlactatemia) had the highest sensitivity (92.3%) and specificity (100%) for predicting mortality (p<0.001). Conclusion: In critically ill children, lactate level of ≥2.95 mmol/L is a good predictor of mortality.